Robson, Martin Britain, Portugal and South America in the Napoleonic Wars. Alliances and Diplomacy in Economic Maritime Conflict. London, I.B. Tauris, 2011. (336 p.) ISBN: 978184885 196 2 - Ortega, René (Estudios Avanzados, 2013)
Robson, Martin Britain, Portugal and South America in the Napoleonic Wars. Alliances and Diplomacy in Economic Maritime Conflict. London, I.B. Tauris, 2011. (336 p.) ISBN: 978184885 196 2